Adaptation and validation of a German version of the Multimorbidity Treatment Burden Questionnaire - Schulze, Josefine; Breckner, Amanda; Duncan, Polly; Scherer, Martin; Pohontsch, Nadine Janis; Lühmann, Dagmar (Health and quality of life outcomes, 2022)
Patients with multiple long-term conditions often face a variety of challenges arising from the requirements of their health care. Knowledge of perceived treatment burden is crucial for optimizing treatment. In this study, we aimed to create a German version of the Multimorbidity Treatment Burden Questionnaire (MTBQ) and to evaluate its validity.